Roman-period and Byzantine Nazareth and its hinterland - Dark, K. R. (Ken R.), author.
1 online resource (pages cm.).
Keywords: "This book presents a new social and economic interpretation of Roman-period and Byzantine Nazareth and its hinterland as a whole, showing the transformation of a Roman-period Jewish village into a major Byzantine Christian pilgrimage centre. Although Nazareth is one of the most famous places in the world, this is the first book on Roman-period and Byzantine Nazareth by a professional archaeologist, the only book to consider the archaeology of Nazareth in the context of its adjacent landscape, and the first to use contemporary archaeological methods and theory to explore Nazareth's archaeology. Taking as his starting point a systematic survey of the valley between Nazareth and the Roman town of Sepphoris, Dark offers an interpretation of communities elsewhere in the Roman world as networks of interlocking cells, with interactions along routeways being more important in cultural and economic terms than the relationship between urban centres and their surrounding countryside. His conclusions have implications for the wider archaeology of the Roman and Byzantine worlds, as well as for archaeological theory, and demonstrate the importance of Nazareth to world archaeology. This unique book will be invaluable to those interested in Nazareth and its surrounds, as well as to archaeologists and scholars of the Roman and Byzantine worlds"--